2011
DOI: 10.1093/bja/aeq346
|View full text |Cite
|
Sign up to set email alerts
|

Intubating conditions and adverse events during sevoflurane induction in infants

Abstract: In 1- to 24-month-old infants, the addition of 0.3 mg kg⁻¹ rocuronium to 8% sevoflurane improved intubating conditions and decreased the frequency of respiratory adverse events. Alfentanil provided no additional benefit in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 27 publications
0
31
0
2
Order By: Relevance
“…The age range of children enrolled in the studies using sevoflurane induction of anesthesia was 12–120 months; one study included children aged 1–24 months (10) (Table 1). The age range of children enrolled in the studies using propofol induction of anesthesia was 12–180 months (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age range of children enrolled in the studies using sevoflurane induction of anesthesia was 12–120 months; one study included children aged 1–24 months (10) (Table 1). The age range of children enrolled in the studies using propofol induction of anesthesia was 12–180 months (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…(10), who reported respiratory or hemodynamic events in 11 of 27 (40.1%) patients in the saline group and in 12 of 23 (52.2%) patients in the alfentanil group. Failed intubations at first attempt were reported in three of the nine studies (9–11) (Table 1), which represent a total of 16 failed intubations at first attempt and an incidence of 2.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While NMBA can reduce the risk of laryngospasm at the time of tracheal intubation [62], a large observational cohort study demonstrated a greater incidence of laryngospasm in the postoperative period [8]. Maintenance of anesthesia with sevoflurane, propofol, or isoflurane is associated with a significantly smaller incidence of laryngospasm compared with desflurane, which should be avoided in children (see also under bronchospasm) [8,63].…”
Section: Anesthetic Agentsmentioning
confidence: 99%
“…A controversial and perhaps more appropriate question is the use of muscle relaxants in the management of the difficult pediatric airway vs maintenance of spontaneous respiration. The use of muscle relaxant to facilitate intubations in infants and children in conjunction with Sevoflurane anesthetic was associated with fewer adverse respiratory events . The decision to administer muscle relaxant is contingent on the underlying airway pathology and expected ability to perform mask ventilation.…”
Section: Anesthetic Management For Difficult Pediatric Airwaymentioning
confidence: 99%